Primary immunodeficiency disorders : a historic and scientific perspective - Etzioni, Amos; Ochs, Hans D. (Academic Press, 2014)
Primary Immunodeficiency Disorders: A Historic and Scientific Perspective provides a complete historical context that is crucial for students and researchers concerned with primary immunodeficiency. When researchers have a poor understanding of the way we arrived where we are in research, they can miss important points about a disease, or miss out on how to approach new diseases. This historical knowledge of research can assist greatly by showing how it was done in the past, demonstrating the successes and failures, so that it can be done better in the future. This book provides an unders.